A phase 1 study to assess the safety, tolerability, and pharmacokinetics of CXD101 in patients with advanced cancer. Issue 1 (17th October 2018) - Eyre, Toby A.; Collins, Graham P.; Gupta, Avinash; Coupe, Nicholas; Sheikh, Semira; Whittaker, John; Wang, Lai Mun; Campo, Leticia; Soilleux, Elizabeth; Tysoe, Finn; Cousins, Richard; La Thangue, Nick; et al.
Abstract: Background: In the current study, the authors sought to determine the maximum tolerated dose (MTD) of the novel class 1 selective histone deacetylase inhibitor CXD101 in a dose escalation study in patients with advanced solid tumors or recurrent/refractory lymphoma. Methods: The authors escalated the dose of CXD101 from 1 mg twice daily orally for 5 days in a 21‐day cycle (3+3 design). Results: A total of 39 patients were enrolled, 36 of whom received CXD101. Of the 30 patients in the escalation cohort, 29 were evaluable for determination of the dose‐limiting toxicity (DLT). DLTs were noted at doses of 16 mg twice daily (1 of 6 patients), 20 mg twice daily (1 of 6 patients), and 24/25 mg twice daily (2 of 5 patients, both of whom developed neutropenic fever). The MTD was 20 mg twice daily, which achieved maximal plasma concentrations (±standard deviation) of 231±76 nM to 342±126 nM, which was within the biologically active range. Six patients received 20 mg twice daily in an expansion cohort. The most frequent adverse events were fatigue, nausea, and reversible cytopenia. Key grade 3 to 4 adverse events (according to Common Terminology Criteria for Adverse Events criteria [version 4.03]) included thrombocytopenia (11%), neutropenia (17%), and neutropenic fever (2%) across the 133 CXD101 cycles given. The toxicity profile was similar to that of licensing studies with other histone deacetylase inhibitors. In 22 evaluable patients receiving a dose of ≥16 mg twice daily (17 of whom had lymphoma and 5 of whom had solid tumors), 3 partial responses (2 in patients with classic Hodgkin lymphoma after allogenic stem cell transplantation and 1 in a patient with angioimmunoblastic T‐cell lymphoma) and 1 complete response (in a patient with follicular lymphoma) were noted (overall response rate of 18%) in addition to 9 patients who achieved durable stable disease. Responses were noted predominantly among patients with lymphoma (tumor reduction noted in 63% of patients on standard computed tomography). Conclusions: The MTD in the current study was found to be 20 mg twice daily. Encouraging and durable activity was observed in patients with Hodgkin lymphoma, T‐cell lymphoma, and follicular lymphoma. Abstract : In the current study, the authors determine the maximum tolerated dose and recommended phase 2 dose of a novel, class 1–specific histone deacetylase inhibitor, CXD101, in a 3+3 design, dose escalation, phase 1 trial. Impressive and durable responses in patients with recurrent/refractory Hodgkin lymphoma, T‐cell lymphoma, and follicular lymphoma are noteworthy and a preliminary assessment of the biomarker HR23B is performed.